2022
DOI: 10.33395/owner.v7i1.1372
|View full text |Cite
|
Sign up to set email alerts
|

Urgensi Nilai Perusahaan: Antara Relevansi Earning Per Share, Struktur Modal dan Kebijakan Dividen

Abstract: Firm value is one of the measurements used to gain the trust of investors and creditors. A high company value will make investors believe in investing their capital or investing in a company, because a high company value indicates high shareholder prosperity indirectly. This study aims to determine whether there is influence between earnings per share (EPS), capital structure, and dividend policy on firm value. The companies studied are consumer goods companies listed on the Indonesia Stock Exchange in 2018 – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…As the company's sales increase, the profits earned by the company will automatically increase or grow. If profits increase, the profits achieved also increase (Effendi, 2022c). Based on the above definition, it can be concluded that growth is an indication of whether a company is progressing or not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the company's sales increase, the profits earned by the company will automatically increase or grow. If profits increase, the profits achieved also increase (Effendi, 2022c). Based on the above definition, it can be concluded that growth is an indication of whether a company is progressing or not.…”
Section: Literature Reviewmentioning
confidence: 99%